(untitled) (International journal of medical sciences, 2025)
Yakson, meaning “the caring hand,” is a traditional Korean method of gentle touch used historically to soothe distress, reduce tension, and foster emotional bonding. While Yakson has been practiced for centuries, its mechanisms are increasingly examined within biomedical and clinical frameworks. Recent scholarship suggests that subtle microchannel networks located between the skin and muscular fascia may play a mediating role in how touch influences the autonomic nervous system, circulatory flow, and somatic tension patterns. This article provides an expanded clinical interpretation of Yakson therapy, focusing on the relationship between skin mechanoreceptors, subcutaneous fascial microchannels, and muscular tone regulation. Two original anatomical diagrams are included to clarify the layered organization and distribution of microchannels. The essay argues that Yakson may be meaningfully incorporated into family medicine as a supportive, non-pharmacological approach to managing stress-related somatic complaints.